Machinability enhancement of heat-treated Incoloy 800H during turning using laser-textured carbide inserts under semi-solid MoS₂ lubrication - Palanisamy Angappan; Palanisamy Duraisamy; Prakash Chellamuthu; Abhishek Agarwal; Lenin Kasirajan (PLoS ONE, 2026)
Incoloy 800H is an iron–nickel–chromium based superalloy widely used in high-temperature applications, but its poor machinability due to rapid work hardening and low thermal conductivity makes machining difficult. This study experimentally investigates the machinability of heat-treated Incoloy 800H during CNC turning using laser-textured tungsten carbide cutting inserts combined with semi-solid MoS₂ lubrication. Four tool configurations were examined: non-textured (NT), parallel-textured (PT), elliptical-textured (ET), and semi-elliptical-textured (SCT) inserts. Turning experiments were performed by varying cutting speed (35–55 m/min) and feed rate (0.02–0.06 mm/rev) while maintaining a constant depth of cut of 1 mm. Machining performance was evaluated through surface roughness, cutting force, cutting power, specific energy consumption, specific cutting pressure, tool-tip temperature, and material removal rate. The results indicate that the parallel-textured tool exhibited superior machining performance compared with the other inserts. The lowest surface roughness of 0.30 µm, cutting force of 91.23 N, and tool-tip temperature of 73.2 °C were obtained with the PT insert under optimal cutting conditions. The improved performance is attributed to reduced tool–chip contact length and enhanced lubrication at the interface provided by the textured surface combined with MoS₂ lubrication. Scanning electron microscopy and energy-dispersive X-ray analysis confirmed diffusion and abrasion as the dominant tool wear mechanisms. The findings demonstrate that the combined application of laser surface texturing and semi-solid MoS₂ lubrication significantly improves the machinability of Incoloy 800H during turning operations. The study provides experimental evidence that parallel-oriented surface textures effectively reduce tool–chip contact length and frictional interaction, thereby enhancing machining performance for difficult-to-cut superalloys.